PENGARUH PAJAK DAERAH, RETRIBUSI DAERAH DAN DANA ALOKASI KHUSUS TERHADAP PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI JAWA TENGAH PERIODE 2015-2019 - Kristanti Rahman; Asih Yuliani Zubaedah (Jurnal Inovasi Daerah, 2022)
This study was conducted with the aim of knowing and analyzing the effect of local taxes, regional retribution and special allocation funds on economic growth (a case study in districts/cities in Central Java). The sample of this study was determined using purposive sampling method. The type of data used was secondary data. In which the total samples selected in this study were 10 districts/cities. The data analysis method used is multiple linear regression analysis. The results of this study indicate that regional taxes and special allocation funds partially have no effect on economic growth, regional retribution has an effect on economics growths, and the influence of local taxes, regional retribution, special allocation funds have no effect on economic growth simultaneously. Further research is suggested to be able to expand the research sample, add variables, and extend the research period.